半導體晶圓代工產業工程師 資訊行為之研究 Information Behavior of the Semiconductor Foundry Industry Engineers - Yu-Ping Shih; Hao-Ren Ke (Jiàoyù zīliào yǔ túshūguǎn xué, 2010)
本研究以某半導體晶圓代工產業公司工程師為研究對象，透過問卷調查及深度訪談來了解工程師之資訊行為。本研究結果發現：㈠半導體晶圓代工產業工程師之資訊需求目的以提升自我工作能力及解決日常工作為主；㈡工程師之資訊搜尋以文件管道及人際關係管道為主要資訊來源管道，尋找資料過程中最常遭遇到的困難為資訊過載及找不到相關專業資訊；㈢資訊品質及資訊取得容易度為工程師尋求資訊時優先考慮的因素，而取得資訊是否符合需求及資訊之正確性為工程師評估資訊的主要考量點，取得資訊後工程師使用資訊的主要目的為提升工作效率，即時且迅速達成目標或任務；㈣工程師之學歷、職銜，以及工作性質對若干資訊行為有顯著影響。 This article takes semiconductor foundry industry engineers as research subjects, and tries to understand their information behavior. This article employs the questionnaire and in-depth interview as the research methodology. There are four primary findings: (1) the information need of an engineer lies in enhancing self’s working-ability and solve problems encountered in daily job; (2) the primary information sources of engineers are documents and interpersonal relationships, and the most difficult problems in seeking information are information overload and too little relevant and professional information; (3) quality and accessibility is the main factor when engineers seek information; whether the information fit demands or not and the information accuracy are the primary points when engineers evaluate information; the main purpose of engineers using information is to work more efficiently and to achieve the goal or mission in a timely manner; (4) the engineers’ educational backgrounds, professional titles, and job functions have significant influences on a few activities of information behavior.